ANALISIS DETERMINAN STRESS DAN PENGARUHNYA TERHADAP KINERJA KARYAWAN DAN TURNOVER INVENTION: STUDI KASUS LEMBAGA KEUANGAN PERBANKAN DAN NON PERBANKAN DI SURABAYA - Novarinda Vanny Kusuma Putri; Sundjoto; Sri Rahayu (MANAJEMEN DEWANTARA, 2024)
Stress is something that can be experienced by employees and staff who work in any sector (education, health or economic sectors). This research analyzes stress through the variables 1) Role Overload, (2) Role Conflict,(3) Role Ambiguity, (4) Work Family Conflict which influences Turnover Invention through the influence of the Performance variable. This research used a total of 240 respondents who were divided into 5 characteristics, namely Age, Gender, Position, Age and Education Level. The results of this research are that Role Overload, Role Conflict, Role Ambiguity and Work Family Conflict have a negative effect on Performance. On the other hand, the stress variable has a positive effect on Turnover Invention. Employee performance has a negative effect on Turnover Invention. Keywords: Stress, Performance, Turnover Invention